PENGARUH ELISITOR KITOSAN TERHADAP KANDUNGAN WITHANOLID TUNAS IN VITRO AKSESI TANAMAN Physalis angulata DARI PULAU MADURA - Retno Mastuti; Jati Batoro; Budi Waluyo (Jurnal Tumbuhan Obat Indonesia, 2021)
ABSTRACT Chitosan is often applied to in vitro culture systems to induce the biosynthesis of a plant's secondary metabolites. The accumulation and profile of secondary metabolites of the same plant species growing in different environments can vary. This study aims to identify and measure withanolide compounds of in vitro shoots of Physalis angulata accessions. Samples obtained from three regions in Madura Island, namely Sampang (A1), Sumenep (A2 and A4), and Pamekasan (A5). Withanolide compounds of in vitro shoots derived from different types of explants after treated with chitosan were also identified and measured. In vitro nodal and apical shoot explants were used for shoot induction on MS medium + BAP 2 mg/L + 0.05 mg/L IAA. In vitro shoots were elicited for six weeks in the shoot induction medium supplemented with 125 mg/L chitosan. Subsequently, in vitro culture of shoots regenerated from explants of nodal (B) and apical shoots (C) without (B1) and with (B2 and C) elicitation of chitosan were extracted and analyzed by HPLC to detect and measure the withanolide compounds. In vitro shoot extracts from all regions contained 38 types of withanolide compounds. The level of the withanolide compound in each region was different. Chitosan increased withanolide levels in vitro shoots regenerated from nodal explant A1, A2, and A4. The withanolide level in vitro shoot regenerated from apical shoot explants A1 and A4 were higher than that in A2 and A5. These results indicated that the in vitro shoots of P. angulata plant accession in Sampang, Sumenep, and Pamekasan had different levels of withanolide. Chitosan was able to increase the accumulation of withanolide compounds in vitro shoots of P. angulata. The types of explants showed different responses in the synthesis and accumulation of withanolide. This study showed that in vitro systems can be used to produce P. angulata plants and increase the level of withanolides compounds. These results indicated that the use of the in vitro system was able to supply P. angulata and withanolide production to support the supply of traditional medicine raw material. Keywords: accession, chitosan, elicitor, Physalis, withanolides ABSTRAK Elisitor kitosan sering digunakan pada tanaman untuk menginduksi biosintesis senyawa metabolit sekunder secara in vitro. Akumulasi dan profil senyawa metabolit sekunder spesies tanaman sama yang tumbuh di lingkungan berbeda dapat bervariasi. Penelitian ini bertujuan untuk mengidentifikasi dan mengukur senyawa withanolid pada tunas in vitro aksesi Physalis angulata yang diperoleh dari tiga wilayah di Pulau Madura, yaitu Sampang (A1), Sumenep (A2 dan A4) dan Pamekasan (A5). Senyawa withanolid pada tunas in vitro yang berasal dari jenis eksplan yang berbeda setelah dielisitasi dengan kitosan juga diidentifikasi dan diukur. Eksplan nodus dan tunas apikal in vitro digunakan untuk induksi tunas pada medium MS + BAP 2 mg/L + IAA 0,05 mg/L. Tunas in vitro dielisitasi selama enam minggu di medium induksi tunas yang ditambah dengan kitosan 125 mg/L. Selanjutnya kultur tunas in vitro hasil regenerasi eksplan nodus (B) dan tunas apikal (C) tanpa (B1) dan dengan (B2 dan C) elisitasi kitosan diekstrak dan dianalisis dengan HPLC untuk mendeteksi dan mengukur senyawa withanolidnya. Ekstrak tunas in vitro dari semua wilayah mengandung 38 jenis senyawa withanolid. Jenis withanolid yang sama menunjukkan kadar yang berbeda di setiap wilayah. Kitosan meningkatkan rata-rata kadar withanolid tunas in vitro hasil regenerasi eksplan nodus dari wilayah A1, A2 dan A4. Tunas in vitro hasil regenerasi eksplan tunas apikal setelah elisitasi menunjukkan kadar withanolid lebih tinggi pada aksesi A1 dan A4, tetapi lebih rendah pada aksesi A2 dan A5. Pada penelitian ini diketahui bahwa tunas in vitro setiap aksesi dari setiap wilayah di Pulau Madura memiliki kadar withanolid yang berbeda. Elisitor kitosan mampu meningkatkan akumulasi senyawa withanolid pada tunas in vitro P. angulata. Jenis eksplan memberikan respons berbeda pada sintesis dan akumulasi withanolid. Hasil ini menunjukkan bahwa pemanfaatan sistem in vitro berpeluang untuk penyediaan bahan tanam P. angulata maupun produksi withanolid dalam rangka mendukung penyediaan bahan baku jamu. Kata kunci: aksesi, elisitor, kitosan, Physalis, withanolid